PENGARUH KUALITAS SEKOLAH DAN HARGA TERHADAP KEPUASAN KONSUMEN SERTA DAMPAKNYA PADA WORD OF MOUTH - Wahyudi Wahyudi; Liza Nora (MIX: JURNAL ILMIAH MANAJEMEN, 2017)
Abstract : This study aims to analyze whether there is a significant influence between school quality and price on customer satisfaction and its impact on word of mouth (Study on Ar-Rahman Islamic School). The research method used is quantitative with survey method. The population is all parents who send their children to school in ArRahman Islamic School which amounts to 400 people. The sample of the research was 200 people,the sample using probability sampling technique ie proportionate stratified random sampling. Data analysis technique with Stuctural Equation Model (SEM) method using AMOS 22.0. The result of the research indicate that there is direct influence and indirect influence, the direct influence consists of: (1) the quality of the school has no significant effect on the WOM, (2) the quality of the school has a significant effect on the consumer satisfaction, (3) the price has significant effect on WOM, (4) ) Price has a significant effect on customer satisfaction and (5) consumer satisfaction has a significant effect on WOM. While the indirect effect consists of: (1)the quality of schools significantly influence the WOM through consumer satisfaction and (2) the price significantly influence the WOM through customer satisfaction.Keywords : School Quality, Price, Consumer Satisfaction and Word of Mouth.